Challenges in Quranic Memorization for Learners with Disabilities - Thuwaiba Thuwaiba; Ibnu Muhammad Yamudin Salaeh (International Islamic Studies Development and Research Center (IISDRC), 2025)
Tahfiz Alquran is a core tradition in Islamic education requiring consistency, repetition, and accuracy of recitation. For learners with disabilities, however, the process presents complex challenges, including sensory limitations, communication barriers, and restricted access to learning media. This study aims to identify and analyze the main challenges faced by disabled learners in Quranic memorization and to formulate supporting factors that enhance the effectiveness of inclusive tahfiz learning. A descriptive qualitative approach was employed, combining literature review and field observation in inclusive tahfiz institutions. Data were collected through interviews with tahfiz teachers, document analysis (Braille Quran, sign-language Quran), and observation of audio-, visual-, and tactile-based learning practices. The findings reveal that the main challenges include limited learning media, insufficient teacher training in Braille and sign language, communication barriers in recitation, and lack of social support. Supporting factors such as spiritual motivation, intensive repetition, and digital technologies were found to accelerate memorization. The implications emphasize the need for disability-friendly tahfiz curricula, teacher training in specialized skills, and strengthened support from families and Islamic educational institutions. These findings can serve as a reference for pesantren, special schools, and tahfiz institutions in designing inclusive and sustainable Quranic memorization programs.